Survival period of field isolates of Trypanosoma vivax in refrigerated blood - Ekwuruke, J.O.; Ikede, B.O.; Opasina, B.A. (1985)
Examines sheep and goats naturally infected with trypanosoma vivax for trypanosome scores during a routine screening at Fasola in Southwest Nigeria. Compares trypanosome survival in goat and sheep blood.